Вивчення динаміки вивільнення протизапального препарату амізону з полімерної лікарської форми на основі гідрофільного блок-кополіуретану, який містить кополімер N-вінілпіролідону з вініловим спиртом - Мазур, Л.М.; Рожнова, Р.А.; Галатенко, Н.А.; Нечаєва, Л.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
The amizonum release kinetics from polyurethane compositions into a physiological solution has been studied in vitro. The introduction of the copolymer of N-vinylpyrrolidone and vinyl alcohol in the structure of the polymeric carrier to cause the more complete yield of a medicinal substance has been shown. The biocompatibility of the obtained polymeric drug form has been investigated by the tissue culture method.